OPTIMALISASI SYIRKAH DALAM PENINGKATAN EKONOMI UMAT BERBASIS AL-QUR’AN - Muhammad Ali, Zulkarnain; Miarti, Sri (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2022)
There are 237 million Muslims in Indonesia, 86.9% as of 2021 from 273 million people. Meanwhile, Indonesia's wealth is managed and controlled not by Muslims, even though there are Islamic businessmen/financial institutions, but in business practice the developed contracts are buying and selling contracts (murabahah) not cooperation contracts (musyarakah). The author is moved to make a study that discusses the meaning of syirkah and its concept in Islam, and how syirkah can improve the people's economy. This research is a qualitative research with library research method, while the analysis used is descriptive analysis. The results of this study indicate that syirkah is one of the Islamic Shari'a in the field of muamalah whose implementation has been exemplified by the Prophet Muhammad and his noble companions, so that understanding of syirkah must be disseminated to the public, and carried out with the right guidelines according to the Shari'a in order to improve the economy of the people. .